Triniti Menurut Agama Kristian - Mohd. Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 1995)
Christianity as well as Judaism and Islam is known as a monotheism religion. Accordingly in Christianity "Christ" was revealed as a father for himself and for the mankind. Through his personality as intermediary between god and the community led to the concept of father, son and holy spirit as one god. This concept is known among the Christianity as the doctrine of trinity or tri-unity. However, Christianity as always being accepted as a so called religion of the heart based on the concept of man - god - jesus but the truly unity of god is a cardinal doctrine of Christianity which is indeed essentially monotheistic. Therefore, this article attempts to describe the doctrine of trinity according to Christians' belief.